ID: 240. Issue 1 (November 2015) - Paijo, Jennifer; Döring, Marius; Spanier, Julia; Grabski, Elena; Garbe, Annette; Messerle, Martin; Hornung, Veit; Kaever, Volkhard; Kalinke, Ulrich
<x xml:space="preserve">Abstract</x> The majority of the human population is latently infected with human cytomegalovirus (HCMV). In the immunocompromised host HCMV reactivation can lead to serious symptoms and vertical infection can cause severe disabilities in the infant. We addressed the susceptibility of primary human antigen presenting cells to HCMV infection and their capacity to mount type I interferon (IFN-I) responses. HCMV treated plasmacytoid dendritic cells (pDC) did not efficiently support viral gene expression, while abundant to intermediate viral gene expression was detected in M-CSF macrophages (M-CSF M<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7n1v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Φ)</alternatives>, monocyte-derived DC (moDC), and GM-CSF macrophages (GM-CSF M<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7n1v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Φ)</alternatives> in descending order. Even though HCMV encodes multiple evasion mechanisms, several of which exploit the interferon system, the magnitude of IFN-I responses mounted by the different monocyte-derived subsets correlated with the degree of infection. In contrast, pDC that were largely resistant to HCMV infection showed the highest IFN-I expression. These data implied that pDC sensed HCMV in a different manner than monocyte-derived cells. Since microbial dsDNA can activate cyclic GMP/AMP synthase (cGAS) to produce cyclic GMP-AMP dinucleotides (cGAMP), which trigger the stimulator of interferon genes (STING) that in turn induces IFN-I, we analyzed cGAS-dependent IFN-I responses in pDC, moDC, GM-CSF M<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7nx6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Φ</alternatives>, and M-CSF M<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7nx6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Φ</alternatives>. We found that upon HCMV infection monocyte-derived macrophages and DC, but not pDC, showed enhanced cGAMP production as a measure of cGAS activity. Moreover, monocyte-derived cells devoid of cGAS showed impaired IFN-I responses. Thus, HCMV stimulated primary monocyte-derived macrophages and DC, but not pDC, showed cGAS dependent cGAMP formation that triggered IFN-I.